Marbofloxacin Influence on Haemato-biochemical Alterations in Diarrheic Calves Infected with Salmonella spp. - Mohamed, Haidy E.; Ibrahim, Hala N.; Ibrahim, Ghada A. (Journal of Advanced Veterinary Research, 2023)
Salmonella spp.; a major zoonotic pathogen worldwide could cause serious diseases that hinder the productivity in calf farms. This study discussed the antibacterial efficacy of the Marbofloxacin drug in calves affected with Salmonella spp. and how it impacted the animal bodyâ€™s haemato-biochemical changes. Salmonella spp. was isolated from diarrheic cases (18.8%) along with other bacteria which were also isolated in varying degrees. Salmonella isolates exhibited multiple serovarsâ€™ identities. Also, they exhibited a multidrug resistant (MDR) pattern. Moreover, PCR approach confirmed both genotypic and phenotypic resistance traits of highly virulent MDR Salmonella isolates. In a trial to evaluate the anti-Salmonella effect of the Marbofloxacin drug, three groups of calves were divided; the first group (G1) was diarrheic without any drug administration, the second (G2) was diarrheic but intramuscularly administered with Marbofloxacin (2ml/50 Kg B.W.) while the control (healthy) group was (G3). The haemato-biochemical results of Salmonella infected group recorded significant increases in RBCs count, PCV, Hb, and leukocytes with marked neutrophilia, monocytosis, and lymphopenia. Moreover, high rates of AST, ALT, urea and creatinine were recorded as well as serum globulin (P<0.05) was extremely increased. Also, a high increase of serum potassium but with notably limited levels of both glucose and sodium was stated. Meanwhile, after treatment, all haemato-biochemical and mineral parameters in G2 were completely improved. In conclusion, the Marbofloxacin drug impacted positively on animal health and in vitro, it completely overcomes calf Salmonella infection which in turn enhances the growth curves of these animals and considerable financial profits. Â